(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Additive manufacturing technology has a quickly expanding ability to replace some of the current traditional processes in research and production. Additional production means that construction components are produced by layer by layer, which directly from a computerized design (CAD) model provide three-dimensional physical models. In a short period, with higher accuracy, the additive production process will manufacture completely dense metal components. The selective SLS technique uses a powder bed fusion in which a laser or electron beam is fused selectively to each powder bed sheet. It is the most promising industrial additive technology for the small to medium volume manufacturing, basic and complex metal components. This review highlights SLS technology’s changes, existing state and obstacles. The paper focused on the SLS technology processed metal content. It also speaks in terms of advantagesdisadvantages, components, machinery and implementations regarding SLS technique.